Progress and perspectives: fluorescent to long-lived emissive multifunctional probes for intracellular sensing and imaging. Issue 16 (8th April 2022) - Jaiswal, Shilpi; Das, Subhadeep; Kundu, Subhankar; Rawal, Isha; Anand, Prashant; Patra, Abhijit
Abstract : We delineated the underlying design strategies and photophysical pathways involved in multifunctional luminescent probes for intracellular sensing and imaging. Abstract : The development of luminescent probes has gained significant interest in real-time intracellular sensing and imaging of various biologically relevant species. The accuracy in sensing and imaging circumventing the background signals due to autofluorescence is essential to decipher subtle changes in cellular microenvironments under diverse pathophysiological conditions. In this context, luminescent probes for background-free imaging demands rational molecular design strategies along with various optical features like lower energy and multiphoton excitation, larger Stokes or anti-Stokes shift, and long-lived emission. Multiphoton microscopy employing two-photon absorbing molecular materials and upconversion nanoprobes is beneficial for deep-tissue imaging. In contrast, organic long-lived emissive probes, including thermally activated delayed fluorescence and room temperature phosphorescence materials, provide promising scope for time-gated imaging, ruling out the dependency on probe concentration and laser power. On the other hand, bioluminescent and chemiluminescent molecular probes producing excited-state emissive species without any optical excitation are emerging candidates for autofluorescence-free intracellular sensing and imaging. In this review article, we delineate versatile design strategies, including the choice of luminescent cores, targeting units, and sensing sites, for the development of multifunctional probes with improved intracellular sensing and imaging. Moreover, a brief discussion of different photophysical pathways involved in signalling processes is provided. The current challenges in targeted intracellular delivery of the probes for non-invasive sensing and imaging are indicated. Finally, we emphasize the future prospects of multiphoton excitable or self-illuminating long-lived emissive probes with state-of-the-art super-resolution microscopy techniques for intracellular sensing and imaging with nanoscale resolution.